2017
DOI: 10.11648/j.ejpm.20170501.11
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Vitamin Deficiencies and Cardiovascular Disease Risk: Advancing Current Understanding

Abstract: Cardiovascular diseases are responsible for one-third of all deaths in the world. Several factors contribute to the current trend including micronutrient vitamin deficiencies (MVDs), however, opinions regarding the role of MVDs in CVDs are inconsistent; this could impact on micronutrient vitamins intake. The aim of this review was to provide a brief overview of published evidence on the associations between MVDs and CVDs, assess the interactions between micronutrients and cardiovascular endpoints, and identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 146 publications
(211 reference statements)
0
16
0
Order By: Relevance
“…It is not possible to conclude from the current study if these deficiencies are a phenomena specific Northern Colorado children, however, previous reports have indicated that approximately a third of the U.S. population (including children and adults) are at risk for micronutrient deficiencies [ 52 ]. Oxidation of LDL-cholesterol, an initiating step in atherosclerosis, is often concurrent with the production of inflammatory cytokines and decreased nitric oxide levels which lead to vasoconstriction and compromised vascular structure [ 22 ]. Micronutrients with documented anti-inflammatory, anti-oxidant, and/or immune modulatory effects (e.g., vitamin A, C, D, E, nicotinamide, folate, riboflavin) play significant roles in cardioprotection [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not possible to conclude from the current study if these deficiencies are a phenomena specific Northern Colorado children, however, previous reports have indicated that approximately a third of the U.S. population (including children and adults) are at risk for micronutrient deficiencies [ 52 ]. Oxidation of LDL-cholesterol, an initiating step in atherosclerosis, is often concurrent with the production of inflammatory cytokines and decreased nitric oxide levels which lead to vasoconstriction and compromised vascular structure [ 22 ]. Micronutrients with documented anti-inflammatory, anti-oxidant, and/or immune modulatory effects (e.g., vitamin A, C, D, E, nicotinamide, folate, riboflavin) play significant roles in cardioprotection [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of LDL-cholesterol, an initiating step in atherosclerosis, is often concurrent with the production of inflammatory cytokines and decreased nitric oxide levels which lead to vasoconstriction and compromised vascular structure [ 22 ]. Micronutrients with documented anti-inflammatory, anti-oxidant, and/or immune modulatory effects (e.g., vitamin A, C, D, E, nicotinamide, folate, riboflavin) play significant roles in cardioprotection [ 22 ]. The anti-oxidant vitamin E has demonstrated protection via reduced atherosclerotic plaque formation in animal models, and dietary consumption of foods rich in vitamin E has been associated with lower CVD outcomes in clinical studies [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence indicates that VA regulates metabolic pathways central to the pathogenesis of metabolic syndrome clusters including obesity [71], diabetes mellitus [72], dyslipidemia [73] and cardiovascular disease [7]. Central to the metabolic pathways is the improvement in β-cell mass and function, hence insulin secretion and responses.…”
Section: Vitamin a Defi Ciency And Irmentioning
confidence: 99%
“…Micronutrients consist of vitamins and minerals which are required in small amounts to enhance normal physiological and biochemical processes in the body. They include, but are not limited to, vitamins A, B, C, D and E, calcium, folate, iodine, iron, zinc, chromium, biotin, thiamine, magnesium and selenium as well as many others [7]. They are classi ied as micronutrients not by virtue of functional importance but by virtue of the amount required by the body.…”
Section: Introductionmentioning
confidence: 99%